The London Stock Exchange in the 19th Century: Ownership Structures, Growth and Performance - Larry Neal (Oesterreichische Nationalbank (OeNB), 2006)
Over the course of the nineteenth century the London Stock Exchange evolved from a market dealing primarily in new issues of British government debt to become the preeminent exchange of the first global capital market. By 1914, one-third of the public capital available to investors anywhere in the world was listed and traded on the London Stock Exchange. In contrast to these examples of spectacular growth of the business conducted within the exchange, however, the microstructure of the London Stock Exchange remained remarkably constant over the entire century. The remarkable expansion in scale and diversification of activity in the London Stock Exchange was sustained over the century with such minimal organizational change due to three factors. First, the evolution of the London Stock Exchange's microstructure was path dependent – the initial conditions for membership set the incentives for the owners and operators of the exchange, and these determined how they responded to successive shocks over time. Second, the continued success of the exchange was due to the peculiar structure of property rights in the exchange. Ownership of the exchange by the Proprietors was separated from governance of the operation of the exchange by the Members. Innovations were spurred by the owners of the exchange, who sought constantly to expand the membership. Newer members were then induced to take risky searches for new sources of revenue. This is how foreign securities were added permanently to the listings of the exchange in the 1820s. The third factor, the exchange's insistence on separating members in to two classes – brokers and jobbers (dealers) – with different incentives led to the increasing ineffectiveness of the exchange over time. By the turn of the 20th century, brokers increasingly outweighed jobbers within the membership and exercised their political power to restrict membership, enforce minimum commissions, and confine arbitrage to a limited class of members. In short, the adverse consequences of a self-regulating club of self-interested members began to appear, but only after a century of remarkable growth, innovation, and effectiveness in mobilizing the savings of the world to realize the material benefits of the first industrial revolution.
Keywords: 330